Determinants of operator and patient radiation exposure during cardiac catheterization: Insights from the RadiCure (RADIation reduction during cardiac catheterization using real‐timE monitoring) trial. Issue 7 (28th December 2015) - Christopoulos, Georgios; Papayannis, Aristotelis C.; Alomar, Mohammed; Christakopoulos, Georgios E.; Kotsia, Anna; Michael, Tesfaldet T.; Rangan, Bavana V.; Roesle, Michele; Shorrock, Deborah; Makke, Lorenza; Maragkoudakis, Spyros; Mohammad, Atif; et al.
Abstract : Background: In the RadiCure study 505 catheterization procedures were 1:1 randomized to use or no use of real‐time radiation monitoring. Use of the Bleeper Sv monitor resulted in a significant reduction in operator radiation exposure. Methods: We examined the association between several baseline and procedural parameters with operator and patient radiation exposure using univariable and multivariable analysis in the 505 patients that were enrolled in RadiCure. All baseline demographic and procedure characteristics recorded were included in the univariable analysis. Results: Median fluoroscopy time was 6.2 (2.5–12.5) minutes, median patient air kerma dose was 0.908 (0.602–1.636) Gray and median first operator exposure was 10 (5–22) μSv. For analysis purposes, the 505 procedures were dichotomized based on the median operator exposure (10 μSv) and median patient radiation dose (0.908 Gray). On multivariable analysis, factors associated with high (above median or >10 μSv) first operator radiation exposure included radial access (odds ratio [OR] 5.44, 95% Confidence Interval [CI] 2.88–10.76), chronic total occlusion (CTO) intervention (OR 12.78, 95% CI 4.42–43.60), real‐time radiation monitoring (OR 0.42, 95% CI 0.26–0.66), and use of a radioabsorbent drape (OR 0.53, 95% CI 0.28–0.96). High patient radiation dose (above median or >0.908 Gray) was associated with body mass index>30 kg/m 2 (OR 3.22, 95% CI 1.99–5.29), prior MI (OR 2.26, 95% CI 1.29–4.04), prior cerebrovascular disease (OR 0.34, 95% CI 0.15–0.75), hypertension (OR 2.40, 95% CI 1.05–5.82), prior coronary artery bypass graft surgery (OR 2.46, 95% CI 1.40–4.39) and CTO intervention (OR 12.93, 95% CI 3.28–87.31), but was not associated with real‐time radiation monitoring and use of a radioabsorbent drape. Conclusions: Several clinical and procedural factors are associated with higher patient and operator radiation exposure. Real‐time radiation monitoring and use of disposable radiation shields were associated with lower operator, but not patient, radiation dose. © 2015 Wiley Periodicals, Inc.